2022
DOI: 10.1242/dmm.049444
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-specific Trim44 knockout in rat attenuates isoproterenol-induced cardiac remodeling via inhibition of AKT/mTOR pathway

Abstract: When pathological hypertrophy progresses to heart failure (HF), the prognosis is often very poor. Therefore, it is crucial to find new and effective intervention targets. Here, myocardium-specific Trim44 knockout rats were generated using CRISPR-Cas9 technology. Cardiac phenotypic observations revealed that Trim44 knockout affected cardiac morphology at baseline. Rats with Trim44 deficiency exhibited resistance to cardiac pathological changes in response to stimulation via isoproterenol (ISO) treatment, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…We used WGA to stain cell membranes and observe the morphology of neurons. 29 The brain sections from CKO rats demonstrated a large number of swollen cells that had clear boundaries, and excluded the possibility that cavitation was caused by mechanical or accidental damage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We used WGA to stain cell membranes and observe the morphology of neurons. 29 The brain sections from CKO rats demonstrated a large number of swollen cells that had clear boundaries, and excluded the possibility that cavitation was caused by mechanical or accidental damage.…”
Section: Discussionmentioning
confidence: 96%
“…The main features of oncosis including cellular swelling, organelle swelling, blebbing and increasing membrane permeability, finally result in cavitation. We used WGA to stain cell membranes and observe the morphology of neurons 29 . The brain sections from CKO rats demonstrated a large number of swollen cells that had clear boundaries, and excluded the possibility that cavitation was caused by mechanical or accidental damage.…”
Section: Discussionmentioning
confidence: 99%
“…Heart tissues collected from the euthanized rats were fixed in 10% formalin and embedded in paraffin followed by 3- to 4-μm section preparation. After dewaxing and rehydrating, the tissue sections were stained with H&E according to methods described previously ( 56 ). H&E-stained slides were scanned with ANNORAMIC 250 Flash III DX and imaged using CaseViewer 3.0 software (3DHISTECH Ltd., Hungary).…”
Section: Methodsmentioning
confidence: 99%
“…As genomics research identifies more and more loci associated with human heart failure, resources such as the International Mouse Phenotyping Consortium can help to identify and model pathogenic mutations. Alongside zebrafish, mice and human stem cell-derived in vitro systems, articles in this issue also discuss the use of rats ( Jiang et al, 2023 ; Zhang et al, 2023 ) and pigs ( Salomon et al, 2023 ; Wolf et al, 2023 ) as valuable models with strong translational potential, expanding the array of models to investigate the causes, consequences and cures for heart failure.…”
Section: Developing Characterising and Choosing The Right Modelsmentioning
confidence: 99%
“…The generation and analysis of rats with cardiac-specific knockout of Trim44 by Jiang et al (2023) demonstrated that this protein is important for heart growth under basal conditions, but that it is also an important mediator of cardiac hypertrophy induced by adrenergic stimulation. Their study corroborates the value of tissue-specific knockout approaches in animal models: it enables the identification of the role of a particular gene in the specific organ or tissue of interest.…”
Section: Acquired Heart Diseasementioning
confidence: 99%